2018
DOI: 10.3390/ma11081357
|View full text |Cite
|
Sign up to set email alerts
|

Radial Compressive Property and the Proof-of-Concept Study for Realizing Self-expansion of 3D Printing Polylactic Acid Vascular Stents with Negative Poisson’s Ratio Structure

Abstract: Biodegradable stents offer the potential to reduce the in-stent restenosis by providing support long enough for the vessel to heal. The polylactic acid (PLA) vascular stents with negative Poisson’s ratio (NPR) structure were manufactured by fused deposition modeling (FDM) 3D printing in this study. The effects of stent diameter, wall thickness and geometric parameters of arrowhead NPR structure on radial compressive property of 3D-printed PLA vascular stent were studied. The results showed that the decrease of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…More importantly, the radial and longitudinal size of the stent crimp under deformation temperature and expand at recovery temperature. This phenomenon demonstrates the feasibility of the shape memory effect of PLA as a reliable basic material for 3D printing stents [ 178 ]. Researchers developed a novel biodegradable polymer–graphene composite with dual drug incorporation.…”
Section: Stent Manufacture Techniquesmentioning
confidence: 84%
“…More importantly, the radial and longitudinal size of the stent crimp under deformation temperature and expand at recovery temperature. This phenomenon demonstrates the feasibility of the shape memory effect of PLA as a reliable basic material for 3D printing stents [ 178 ]. Researchers developed a novel biodegradable polymer–graphene composite with dual drug incorporation.…”
Section: Stent Manufacture Techniquesmentioning
confidence: 84%
“…Among them, PLA is widely used to make biodegradable stents due to its excellent biocompatibility and biodegradability. In addition, and the resulted polymeric stents have the mechanical properties perfectly meeting the requirements . Therefore, PLA was selected as the build material.…”
Section: Methodsmentioning
confidence: 99%
“…However, the Arrowed stent is still in the initial stage of research, and its mechanical properties have not been rigorously scientifically studied. The Arrowed stent manufactured by Wu et al [ 119 ] using FDM technology (as shown in Figure 17 a) was of poor quality and required a long time of post-processing. The Ameer team [ 120 , 121 , 122 ] synthesized a new Arrowed degradable polymer stent ( Figure 17 b), and successfully achieved non-supported printing by using a new micro-continuous liquid interface manufacturing technology.…”
Section: Structure Design Of Vascular Stentsmentioning
confidence: 99%